2007
DOI: 10.1071/sb06043
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Prosopis (Leguminosae) as shown by morphological and biochemical evidence

Abstract: Prosopis L. is a rather primitive genus within the Leguminosae-Mimosoideae. This genus has been divided into five sections on the basis especially of the vegetative diversification of the spines. Three of the sections, Algarobia, Monilicarpa and Strombocarpa, are distributed in America. In order to elucidate systematic relationships between the American sections of Prosopis, a morphological and biochemical phylogeny were obtained. Twenty-two morphological characters were scored for 27 species of Prosopis and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…For example, Dichrostachys and allies (Luckow, 1995, and in prep. ;Luckow & al., 2005), the Pithecellobium group (Grimes, 1995); New World Ingeae (Barneby & Grimes, 1996, 1997Barneby, 1998), Desmanthus (Luckow, 1993); Parkia (Luckow & Hopkins, 1995); Acacia (Chappill & Maslin, 1995;Grimes, 1995;Rico Arce & Banks, 2000); Leucaena (Hughes, 1998); Prosopis (Burghardt & Espert, 2007); Caesalpinioideae (Herendeen & al., 2003a); resin-producing Detarieae (Fougère-Danezan & al., 2010), Aphanocalyx-BikiniaTetraberlinia (Wieringa & Gervais, 2003); Swartzieae and Sophoreae (Herendeen, 1995); the Dalbergioid clade ); Diocleinae (Queiroz & al., 2003); Acosmium s.l. (Rodrigues & Tozzi, 2007).…”
Section: Integrating Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Dichrostachys and allies (Luckow, 1995, and in prep. ;Luckow & al., 2005), the Pithecellobium group (Grimes, 1995); New World Ingeae (Barneby & Grimes, 1996, 1997Barneby, 1998), Desmanthus (Luckow, 1993); Parkia (Luckow & Hopkins, 1995); Acacia (Chappill & Maslin, 1995;Grimes, 1995;Rico Arce & Banks, 2000); Leucaena (Hughes, 1998); Prosopis (Burghardt & Espert, 2007); Caesalpinioideae (Herendeen & al., 2003a); resin-producing Detarieae (Fougère-Danezan & al., 2010), Aphanocalyx-BikiniaTetraberlinia (Wieringa & Gervais, 2003); Swartzieae and Sophoreae (Herendeen, 1995); the Dalbergioid clade ); Diocleinae (Queiroz & al., 2003); Acosmium s.l. (Rodrigues & Tozzi, 2007).…”
Section: Integrating Morphologymentioning
confidence: 99%
“…Recent phylogenetic studies of genera include Hoffmannseggia (Simpson & Ulibarri, 2006); Phaseolus (DelgadoSalinas & al., 2006); Paloue and related genera (Redden & Herendeen, 2006); Phyllolobium Fisch. (Zhang & Podlech, 2006); Lotus L. (Degtjareva & al., 2006(Degtjareva & al., , 2008; Piptadenia (Jobson & Luckow, 2007); Prosopis (Burghardt & Espert, 2007;Catalano & al., 2008); Paraserianthes I.C. Nielsen ; Platymiscium Vogel (Saslis- Lagoudakis & al., 2008); Mimosa (Bessega & al., 2008;Simon & al., 2011;Bessega & Fortunato, 2011); Bauhinia s.l.…”
Section: Integrating Morphologymentioning
confidence: 99%
“…Interestingly, the herbivorous teiid C. murinus, on Bonaire, generally avoids leaves of Prosopis juliflora (Dearing and Schall, 1992), possibly because of their high saponin content (Dearing and Schall, 1992). Prosopis juliflora is closely related to P. pallida (Harris et al, 2003;Burghardt and Espert, 2007), but little is known about the presence and abundance of saponin and other secondary metabolites in P. pallida. Prosopis pallida is a nitrogen fixing tree species (Ramírez-Orduñ a et al, 2005), and its leaves are rich in nitrogen (concentration of 3.24 6 0.32%, compared with only 1.50 6 0.30% for the sympatric Capparis scabrida; Havik, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving pollen grain morphology (Caccavari De Filice 1972) and foliar architecture (Martinez 1984) and seed protein electrophoresis (Burghardt and Palacios 1997) have clearly differentiated the species of both sections. Moreover morphological and biochemical data involving seven species from Strombocarpa suggest that it constitutes a natural taxon (Burghardt and Espert 2007), unlike Algarobia. Isozyme and amino acid analysis also show that the genetic and morphological differences are high among species in section Strombocarpa compared to Algarobia (Carman et al 1974;Saidman et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Species of section Algarobia are mostly selfincompatible and outcross (Solbrig and Cantino 1975;Simpson 1977), although a small percentage of selfing is reported (Bessega et al 2000). Enzyme and molecular marker studies have concluded that section Algarobia is not a natural group (Bessega et al 2005;Burghardt and Espert 2007). Although isozyme analysis proved to be useful, the enzymatic expression is restricted to specific developmental stages or tissues influenced by the environment (Solbrig and Bawa 1975;Whitmore and Bragg 1979;Saidman and Vilardi 1987).…”
Section: Introductionmentioning
confidence: 99%